Successful Implementation and Elements of Healthy Food Retail Programs: Extension Professionals Perceptions (P04-167-19). (13th June 2019) - Nussbaumer, Alexandra; Riggsbee, Kristin; Steeves, Elizabeth Anderson; Hall, Elizabeth; Sneed, Christopher; Burney, Janie; Colby, Sarah
Abstract: Objectives: The objective of this cross-sectional, exploratory study was to understand the perceptions of healthy food retail programs (HFRP) by Extension professionals in low-income communities to determine strategies for successful implementation of HFRP. Methods: Thirty Extension agents and county directors from one state in the southeastern U.S. were recruited via emails, and 53.3% ( n = 16) completed a demographics questionnaire and a semi-structured interview. The interviews were conducted and recorded using online video conferencing software and took place in August and September 2018. Participants were asked about their definitions of HFRP, what challenges and benefits they had observed during HFRP implementation in their communities, and to identify strategies that would increase the success of HFRP programs. Recordings were transcribed verbatim and analyzed by two researchers independently using multiple coding mechanisms. Results: Most participants were white (87.5%), female (93.7%), and had worked for Extension for 0–5 years (37.5%). Participants did not have any prior experience with HFRP; therefore, the qualitative data revolved around their interpretation of a HFRP, which varied. Participants noted the following as components needed for a successful HFRP implementation: working in both corporate supermarkets and local mom-and-pop stores; promoting healthy food retail options; and conducting food demonstrations. One emergent theme was that HFRP would bring immense benefits to their communities, including expanding the recognition of Extension and a higher consumption of healthier foods among community members. One barrier identified was current county-level evaluation practices for policy, systems, and environment (PSE) approaches, which Extension staff are evaluated upon, not currently fully capturing HFRP interventions. Adequate training of HFRP was another theme that was identified, with agents requesting in-person, hands-on techniques. Conclusions: Extension staff perceive that HFRP implementation may provide benefits to low-income communities. However, one specific need that was identified is hands-on training prior to initiation of HFRP. Additionally, participants requested new approaches for evaluating PSE programs like HFRP. Funding Sources: No funding sources.